Effect of INS v. Chadha on Section 402 (Jackson-Vanik Amendment) of the Trade Act of 1974. (U.S. Congressional Research., 1990)
Analyzes the Supreme Court decision in Immigration and Naturalization Service v. Chadha that the legislative veto provision in the Immigration and Nationality Act of 1952 is unconstitutional. Assesses the ruling's potential impact on sections of the Trade Act of 1974 which set forth procedures for congressional review of extensions of the President's authority to waive freedom of emigration requirements of the Trade Act.